2010
DOI: 10.1002/app.31908
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and properties of electromagnetic wave shielding polymer materials with low flammability

Abstract: Novel polyethylene-and polypropylenebased electromagnetic wave shielding and absorbing composite materials with low combustibility, enhanced thermal and mechanical properties, containing graphite, grinded wood, and fire retardants, were developed and investigated. Flame-resistance, thermal and mechanical properties of these materials was investigated. Electromagnetic wave reflection coefficients over the frequency range 20-40 GHz were measured; at moderate concentration (10-15%) of functional filler, reflectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Details of experimental techniques are given elsewhere [21]. Oxygen index (OI) of the samples increases when fire retardants, PBMA and OG, are added.…”
Section: To Inhibit Simultaneously Both Thermal and Chain Processes Omentioning
confidence: 99%
“…Details of experimental techniques are given elsewhere [21]. Oxygen index (OI) of the samples increases when fire retardants, PBMA and OG, are added.…”
Section: To Inhibit Simultaneously Both Thermal and Chain Processes Omentioning
confidence: 99%
“…Among these conductive fillers, graphite was deemed as having better commercial prospects due to its very low cost and high conductivity. Research indicated that PE and PP composites with 15% of graphite exhibited the optimal EMI SE of 16 dB and 11 dB in the range 20 to 40 GHz (Volkov et al 2010). But Panwar et al (2010) fabricated the PP/graphite composites using a melt mixing method, and the maximum value of EMI SE was measured to be as high as 44.12 dB at 2.76 GHz for the composites with 25% of graphite.…”
Section: Introductionmentioning
confidence: 99%